พฤติกรรมการแสวงหาสารสนเทศเพื่อการทำวิจัยของบุคลากรมหาวิทยาลัยมหาสารคาม - น้อยบัวทิพย์, มะลิวัลย์ (บรรณศาสตร์ มศว, 2019)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการแสวงหาสารสนเทศ ปัญหาและความต้องการสารสนเทศและการบริการสารสนเทศเพื่อการวิจัยของบุคลากรมหาวิทยาลัยมหาสารคาม รวมทั้งพัฒนาแนวทางการพัฒนาทรัพยากรสารสนเทศและและการบริการสารสนเทศเพื่อการวิจัยของสำนักวิทยบริการ มหาวิทยาลัยมหาสารคาม กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ บุคลากรของมหาวิทยาลัยมหาสารคาม จำนวน 149 คน ซึ่งคัดเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า บุคลากรมหาวิทยาลัยมหาสารคามส่วนใหญ่มีพฤติกรรมแสวงหาสารสนเทศจากแหล่งที่ใกล้และสะดวกในการเข้าใช้ ได้แก่ อินเทอร์เน็ต/ฐานข้อมูลออนไลน์ เครื่องมือที่ใช้ในการแสวงหาสารสนเทศมากที่สุด คือ คอมพิวเตอร์ส่วนบุคคล แหล่งสารสนเทศที่ใช้มากที่สุด คือ เอกสารอ้างอิงและบรรณานุกรมท้ายเล่มหนังสือและบทความวารสาร เกณฑ์การประเมินสารสนเทศที่ใช้มากที่สุด คือ ความน่าเชื่อถือ นอกจากนี้บุคลากรส่วนใหญ่เคยเข้าใช้บริการในห้องสมุดและมีความถี่ในการเข้าใช้ 1-5 ครั้ง/สัปดาห์ ความต้องการและการใช้บริการของห้องสมุดเพื่อการวิจัย พบว่า โดยรวม บุคลากรใช้บริการของห้องสมุดอยู่ในระดับน้อย มีการใช้วัสดุตีพิมพ์อยู่ในระดับปานกลาง ส่วนโสตทัศนวัสดุมีการใช้ในระดับน้อยมาก มีการใช้บริการสารสนเทศเพื่อการวิจัยโดยรวมอยู่ในระดับปานกลาง โดยใช้บริการสอนการสืบค้นสารสนเทศเพื่อการวิจัยอยู่ในระดับมาก บุคลากรส่วนใหญ่ไม่ประสบปัญหาในการแสวงหาสารสนเทศเพื่อการวิจัย สำหรับผู้ที่ประสบปัญหาและอุปสรรค พบว่า บุคลากรไม่ทราบแหล่งสารสนเทศเพื่อการวิจัย ปัญหาสารสนเทศเก่าล้าสมัย และไม่มีสารสนเทศที่ต้องการในห้องสมุด ส่วนแหล่งสารสนเทศอินเทอร์เน็ตและเครือข่ายสังคมออนไลน์ มีปัญหาเรื่องความล่าช้าของสัญญาณอินเทอร์เน็ต บุคลากรมีความต้องการให้สำนักวิทยบริการสนับสนุนการดำเนินการวิจัย โดยต้องการสิ่งพิมพ์อิเล็กทรอนิกส์ในระดับมาก ต้องการใช้บริการสารสนเทศเพื่อการวิจัย ได้แก่ บริการสอนการสืบค้นสารสนเทศเพื่อการวิจัยอยู่ในระดับมาก แนวทางในการพัฒนาทรัพยากรสารสนเทศและบริการสารสนเทศ ได้แก่ การจัดหาทรัพยากรสารสนเทศให้ครอบคลุมทุกสาขาวิชาตามความต้องการของนักวิจัยให้มากขึ้น ทรัพยากรสารสนเทศควรมีรูปแบบอิเล็กทรอนิกส์มากขึ้น และการบริการสารสนเทศเพื่อการวิจัยของบุคลากรควรจัดให้มีบริการสอนการสืบค้นสารสนเทศและบริการเพื่อการวิจัยให้มากขึ้น ABSTRACT This research aims to study the information seeking behavior of Mahasarakham University staffs, in the aspect of the problems and needs of information and information services for research, and to find the guideline for developing information resources and information services of the Academic Resource Center, Mahasarakham University. The samples of this study were 149 university staffs, selected by purposive sampling. The questionnaire was used to collect data and the statistical used to analyze the data were percentage, means and standard deviation. The research findings revealed that: The majority of staffs of Mahasarakham University seek information from internet/ online databases/search engine which is easy to access. They mostly used personal computers (PC) to search for information. Almost of the searching started from reference or a bibliography that appeared at the end of the book / journal and most of information is evaluated by the reliability (author, publisher). Most of staffs used to walk in and access to library services and frequency of access was 1-5 times/week. The level of using information services was found in low level as a whole. Therefore, the information seeking for printed material was in the moderate level, the research report was in high level. But the information seeking for non-printed material was in low level in all types. Most of the staffs used library services in the moderate level and the information retrieval service was at a high level. Most of staffs do not face the problem of seeking information for research. For those who encounter problems and obstacles was found that they do not know where the research are, moreover the problem of information which were old and not up to date, and there was no information needed in the library. In term of Internet resources and networking, there was a problem with the delay of the Internet signal. The majority of staffs wanted the university library support in information resources at the moderate level as a whole. They also needed electronics material, needed to use information services, and needed to use the research information retrieval service for research at a high level as well. The guideline for the development of information resources and library services such as to provide information resources cover all disciplines, based on the needs of the researchers; to acquire the electronic information resources should be electronic in higher ratio than printed and non-printed formats; and to service information for researchers in teaching information retrieval and more. คำสำคัญ: พฤติกรรมการแสวงหาสารสนเทศ ความต้องการสารสนเทศ นักวิจัย มหาวิทยาลัยมหาสารคาม Keywords: Information seeking behavior, Information need, Researcher, Mahasarakham University